Local Wisdom of Community in Land and Forest Fire Prevention (A case Study of Local Community of Kasepuhan Ciptagelar, Sirnaresmi Village Cisolok Subdistrict, Sukabumi District, West Java Province) - Lailan Syaufina; Fransisxo GS Tambunan (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2013)
Forest fire prevention is more important to minimize the impacts of fire occurences when compared to fire suppression. Local community is sometime has their own way to prevent the fire by implement local wisdom The study aimed to identify farmers characteristics and farming system, to study firing techniques in land clearing activities, and to analyse local wisdom of community in forest and land fire prevention. The study was conducted in Kasepuhan Ciptagelar, Sirnaresmi village, Cisolok sub district, Sukabumi district, West Java Province. Data was retrieved based on the perceptions of the respondents which selected by using a purposive sampling technique, field observation, and literature reviews.. Results of the study identified local wisdom of local community of Kasepuhan Ciptagelar related to land and forest fire prevention, namely: always doing burning for land preparationduring the dry season only and no farming activities close to the national park areas.Keywords : local wisdom, prevention, land and forest fire, local community